How College Students Assess the Threat of Infectious Diseases: Implications for University Leaders and Health Communicators (Journal of International Crisis and Risk Communication Research, 2021)
Higher education institutions and their students face a wide range of infectious disease threats (IDTs). However, there is a lack of theory-driven research on how to provide communication for multiple IDTs to motivate protective action taking. To close this gap, this study focuses on college students and two IDT types: respiratory and sexually transmitted infections. We tested an IDT appraisal model with data from an online survey conducted at two U.S. universities with 842 students. Findings indicate that IDT type led to different patterns of threat appraisal and protective action taking intentions. More specifically, participants perceived sexually transmitted threats as significantly more predictable and more controllable than respiratory threats. Participants also had higher intention to take protective action in response to respiratory threats than sexually-transmitted threats. We also found that externalattribution- dependent (EAD) emotions (i.e., anger, sadness, surprise, and confusion) and an internal-attribution-dependent (IAD) emotion (i.e., hope) were sequential mediators in the relationship between IDT appraisal and protective action taking intentions for both infectious disease types. Implications for IDT communication research and practice are discussed.